Draft genome sequence of Rhizobium sophoriradicis H4, a nitrogenfixing bacterium associated with the leguminous plant Phaseolus vulgaris on the coast of Peru - Ormeño-Orrillo E. (2018)
The genome sequence of Rhizobium sophoriradicis H4, a nitrogen-fixing bacterium isolated from the common bean (Phaseolus vulgaris) in Peru, is reported here. The genome assembly revealed a 6.44-Mbp genome which was distributed into 95 contigs, with N50 and L50 values of 293 kbp and 9, respectively. The genome contained 6,312 coding sequence (CDS) genes and 52 RNA genes (49 tRNAs and 3 rRNAs). © 2018 Ormeño-Orrillo et al.